Whither State and Local Finance? - Ecker-Racz, L. L. (Journal of Finance, 1964)
L. L. Ecker-Racz, Whither State and Local Finance?, The Journal of Finance, Vol. 19, No. 2, Part 1: Papers and Proceedings of the Twenty-Second Annual Meeting of the American Finance Association, Boston, Massachusetts, December 27-29, 1963 (May, 1964), pp. 370-381